Epstein–Barr Virus Driven Hodgkin’s Lymphoma after a Short Course of Daratumumab Treatment for Relapsed Multiple Myeloma - Moeen Mohammadi-Oroujeh; Ansa Mehreen; David L. Grinblatt (Case Reports in Hematology)
In this case, we describe the potential risk of developing an infectious complication leading to a secondary malignancy after a short course of immunotherapy. We report a patient who presented with Epstein–Barr virus (EBV) driven Hodgkin’s lymphoma after treatment with a short course of daratumumab along with pomalidomide and dexamethasone for relapsed multiple myeloma. Although there have been limited documented cases of daratumumab treatment leading to EBV reactivation, in patients presenting with infectious symptoms or neutropenia on a daratumumab-based regimen, testing for EBV should not be overlooked.